The relationship between facial morphology, body measurements and socio-economic factors - Jandová, Marie; Urbanová, Petra (Anthropological Review, 2016)
Background and aim: The effect of socio-economic factors (living conditions) and parental smoking habits on development of facial morphology and body measurements was studied on a longitudinal Czech sample of 25 girls and 25 boys.Subjects and methods: A set of studied digitalized photographs taken from 0.5 to 18 years in intervals of 6 months originated in the Brno Longitudinal Study. Facial shape changes of sub-adult participants were described using a configuration of 27 landmarks and further studied by using methods of geometric morphometric and multivariate statistics. In order to localize growth-related shape changes within the face, the studied region was divided into upper, middle and lower facial units and analyzed separately.Results and conclusion: The results show that in the course of ontogenesis there is a strong correlation between facial shape change and body measurements, height included (r=0.10 and r=0.24 in boys and in girls, respectively). The pubertal spurt of the facial shape change rate was revealed at 10.5 years in girls and at 11.5 years in boys. The earlier onset of the pubertal rate increase in facial shape changes in boys was associated with records of poor living conditions. In addition, the mother’s smoking habits were linked to a noticeable facial shape change.